Dynamics of interdependent critical infrastructures - a prioritised distribution model. (30th July 2021) - Klein, Peter
Previous research articles about interdependent critical infrastructures developed different mathematical models describing the dynamic direct and indirect interactions of these infrastructures. Many of these models use discrete time steps to show how a reduced operability of one infrastructure C at time t will lead at time t + 1 to reductions in all infrastructures to which C distributes its output; and many of them use a standard mode of distribution which will be called proportional. According to a recent result, with this proportional distribution a reduced operability in only one infrastructure will lead to an enduring reduction of all operabilities even after full repairs of all damages. This research replaces this proportional mode by a newly defined prioritised one. It shows that a system with prioritised distribution mode leads in nearly all practical cases to an increased behaviour of the whole system: after repair of all damages, all infrastructures will return automatically to full operability.